Optical sensor to improve the accuracy of non-invasive blood sugar monitoring - Aliya Zilgarayeva; Nurzhigit Smailov; Sergii Pavlov; Sharafat Mirzakulova; Madina Alimova; Bakhytzhan Kulambayev; Dinara Nurpeissova (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
Optical sensors offer a painless method of monitoring blood glucose levels using various light technologies to analyze blood characteristics without penetrating the skin. The literature review part reflects the progress in optical sensor technology evaluates its potential in blood glucose monitoring by overcoming the limitations of conventional methods and recognizes the challenges and future prospects in this rapidly developing area of research. The results of empirical studies are then presented. The methodology is presented as a non-invasive method of blood glucose monitoring based on near-infrared spectroscopy. To precisely evaluate blood glucose concentrations, spectroscopy techniques involving absorption and reflection are employed at wavelengths 450, 900, 1350, and 1800 nm. After absorption and reflection of glucose molecules, light is generated. An experimental study of different samples revealed a linear relationship between the final output voltage and sugar concentration. The results demonstrate a correlation between blood glucose level and signal intensity after transmission.